A novel heat-resistant Al–Si–Cu–Ni–Mg base material synergistically strengthened by Ni-rich intermetallics and nano-AlNp microskeletons. Issue 3 (March 2019) - Hu, Kaiqi; Xu, Qingfei; Ma, Xia; Sun, Qianqian; Gao, Tong; Liu, Xiangfa
Abstract: In this work, nano-AlN particle (nano-AlNp ) microskeletons were introduced into an Al–Si–Cu–Ni–Mg alloy by Al–8AlN master alloy in which the nano-AlNp reinforcements connect with each other to form three-dimensional networks. It is found that these nano-AlNp microskeletons mainly distribute in the binary Al–Si eutectic zones resulting in flaky eutectic Si phases being modified to particulates. Meanwhile, the microskeletons strengthen the matrix synergistically with semi-continuous Ni-rich intermetallics in three dimensions. The tensile mechanical properties, micro-hardness and thermal expansion properties of the alloy at different temperatures are significantly improved. Especially, the ultimate tensile strength (UTS) at 350 °C increases from 85 MPa to 106 MPa, rising by 24.7%, which is ascribed to nano-AlNp microskeletons assisting intermetallics with undertaking mechanical loading, and to the modification of eutectic Si phases to reduce the stress concentration at elevated temperatures.